Effectiveness of the Application of Counseling Theory Behavioral with Modeling Techniques to Increase the Desire to Solve Something Well and Successfully Through Lesson Study in Sukasada - Luthfi Fuadi; Ketut Gading; I Ketut Dharsana (RedwhitePress)
This study aims to determine the effectiveness of counseling behavioral Ivan Pavlov with modeling techniques to increase desire to finish things well and succeed through lesson study. To find data using pretest and posttest, the sample of this study was taken using a questionnaire. Data analysis can be concluded that the price tcount = 7.44> 2.02, so Ho is rejected and Ha is accepted. It was concluded that there was a high effectiveness in behavioral counseling Ivan Pavlov using techniques modeling to improve things well and would be successful